2021
DOI: 10.1136/bmj.n1904
|View full text |Cite
|
Sign up to set email alerts
|

Long term exposure to low level air pollution and mortality in eight European cohorts within the ELAPSE project: pooled analysis

Abstract: Objective To investigate the associations between air pollution and mortality, focusing on associations below current European Union, United States, and World Health Organization standards and guidelines. Design Pooled analysis of eight cohorts. Setting Multicentre project Effects of Low-Level Air Pollution: A Study in Europe (ELAPSE) in six European countries. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
71
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 37 publications
(89 reference statements)
10
71
1
3
Order By: Relevance
“…When combined with previous findings,3451011 the findings from this study confirm the direction of effect—increased long term exposure to PM 2.5 increases the risk of mortality, reduced long term exposure to PM 2.5 decreases the risk. The magnitude of the underlying causal effect remains uncertain, however, partly owing to the study’s design.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…When combined with previous findings,3451011 the findings from this study confirm the direction of effect—increased long term exposure to PM 2.5 increases the risk of mortality, reduced long term exposure to PM 2.5 decreases the risk. The magnitude of the underlying causal effect remains uncertain, however, partly owing to the study’s design.…”
supporting
confidence: 88%
“…More research is needed to quantify the magnitude of the reported effects. Nonetheless, the study by Chen and colleagues adds to the now overwhelming body of evidence that long term exposure to PM 2.5 is associated with mortality,3451011 even in countries such as Canada where PM 2.5 levels are considered low by global comparisons. In response to this evidence, the World Health Organization recently introduced new air quality guidelines, which halved the recommended annual PM 2.5 limit (now 5 μg/m 3 ) 13.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a large cohort study comprising eight European cohorts, a positive association was observed between PM 2.5 level and deaths from natural causes. 46 In a US national cohort of about 1.6 million respondents to the national health interview surveys, higher PM 2.5 levels were associated with all cause mortality and mortality from cardiopulmonary causes and lung cancer. 47 Similar associations were reported in a Canadian study using the 2001 CanCHEC.…”
Section: Comparison With Other Studies and Discussion Of Potential Mechanismmentioning
confidence: 99%
“…This study also linked increased PM 2.5 concentrations arising from residential mobility to increased mortality, which is in line with mounting evidence showing the impact of PM 2.5 on increasing mortality in diverse locations, including Europe and north America. For example, in a large cohort study comprising eight European cohorts, a positive association was observed between PM 2.5 level and deaths from natural causes 46. In a US national cohort of about 1.6 million respondents to the national health interview surveys, higher PM 2.5 levels were associated with all cause mortality and mortality from cardiopulmonary causes and lung cancer 47.…”
Section: Discussionmentioning
confidence: 99%